Multiplicity of skin cancers in Queensland and their cost burden to government and patients - Louisa G. Gordon; Thomas M. Elliott; Catherine M. Olsen; Nirmala Pandeya; David C. Whiteman (Elsevier, 2018)
Abstract Objective: To determine the cost burden to government and patients for individuals with multiple skin cancers. Methods: We used self‐reported baseline data on socio‐demographics, phenotype and sun exposure behaviours from participants in the QSkin Sun and Health Study with at least one histopathologically confirmed keratinocyte cancer or melanoma (n=5,673). Linkage to Australian Medicare data (2011-2014) provided resource data and government and out‐of‐pocket patient costs. Generalised linear models examined costs by frequency of skin cancer groups separately for melanoma and keratinocyte cancer. Results: Over three years, 539 participants were diagnosed with melanoma (11% had ≥2 melanomas) and 5,134 participants were treated for keratinocyte cancers (10% had ≥6). Median Medicare costs per person were $1,325 (maximum $6,117) for ≥2 melanomas and $2,126 (maximum $54,618) for ≥6 keratinocyte cancers. Increased costs were associated with private health insurance. Conclusions: Individuals who are multiply affected by skin cancers are relatively common and the accompanying individual and government cost burden can be substantial. These findings support skin cancer being classified as a chronic disease. Implications for public health: Over time, the economic burden for skin cancer for individuals and health providers is high and investment in prevention remains important from an economic viewpoint.